2019
DOI: 10.4269/ajtmh.18-0711
|View full text |Cite
|
Sign up to set email alerts
|

Case Reports: Survival from Rabies: Case Series from India

Abstract: Rabies, a zoonotic viral encephalitis, continues to be a serious public health problem in India and several other countries in Asia and Africa. Survival is rarely reported in rabies, which is considered to be almost universally fatal. We report the clinical and radiological findings of eight patients with laboratory-confirmed rabies who survived the illness. With the exception of one patient who recovered with mild sequelae, all survivors had poor functional outcomes. The reported survival from rabies in recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…Though the number of current survivors is small, an increasing number of survivors are being reported from India in recent years and probabilistically, better outcomes will follow. In fact, 10 patients in this study (7 cases published [33]) have survived beyond 6 months, two of them with good functional outcomes (Table 3).…”
Section: Discussionmentioning
confidence: 85%
“…Though the number of current survivors is small, an increasing number of survivors are being reported from India in recent years and probabilistically, better outcomes will follow. In fact, 10 patients in this study (7 cases published [33]) have survived beyond 6 months, two of them with good functional outcomes (Table 3).…”
Section: Discussionmentioning
confidence: 85%
“…Especially in the case presented here, the chief complaint of chest pain deviated the medical team's attention/focus away from a diagnosis of rabies to heart disease. Though uncommon, such cases have been reported ( Table 2) [4][5][6][7][8] , since rabies can caused focal interstitial myocarditis as discussed by Park et al 9 In the case series reported by Mani et al 10 , all cases presented without evidence of chest pain, so the clinical presentations of rabies vary. Furthermore, concerning the classical sign of fear of water, in our case, the patient 11 In terms of the forensics aspect, since a rabies investigation is not performed on every case with an unknown cause of death examined by only external examination, the forensic physician thought of rabies infection as the cause of death based on the review of the history recorded on the first emergency room visit and the numerous dogs observed by the forensic physician at the crime scene during the post-mortem visit at the patients residence.…”
Section: Discussionmentioning
confidence: 99%
“…The primary reason for these miserable deaths is that a large number of victims do not receive rabies vaccination at all, and some of those who do do not complete the full course. Noticeably, while rabies used to be considered certainly fatal, several rabies survivors have been increasingly reported over the past two decades worldwide, particularly in recent years [5361]. Excellent intensive care facilities and aggressive management approaches with appropriate supportive care are believed to contribute to the increase of human rabies survivors [53].…”
Section: Discussionmentioning
confidence: 99%
“…For example, in India, although public health facilities may be lacking (especially in rural areas), several private and some public medical institutes provide world-class medical care, thus likely playing an important role in the prolonged survival of human rabies patients [53]. Most recently, Mani et al [61] reported two cases whose lives were saved after receiving both rabies vaccine and immunoglobulin and intensive care. However, the patients progressed to clinical disease with typical symptoms of rabies, probably due to multiple exposures or bites on highly innervated areas [61].…”
Section: Discussionmentioning
confidence: 99%